2017
DOI: 10.1111/1462-2920.13720
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic influences exceed dispersal effects on hydrologically‐connected microbiomes

Abstract: Subsurface groundwater-surface water mixing zones (hyporheic zones) have enhanced biogeochemical activity, but assembly processes governing subsurface microbiomes remain a critical uncertainty in understanding hyporheic biogeochemistry. To address this obstacle, we investigated (a) biogeographical patterns in attached and waterborne microbiomes across three hydrologically-connected, physicochemically-distinct zones (inland hyporheic, nearshore hyporheic and river); (b) assembly processes that generated these p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(84 citation statements)
references
References 86 publications
8
75
1
Order By: Relevance
“…A subset of these taxa was present in comparable numbers in all three habitats, whereas others showed major variations connected to differential organic matter input and metabolism. Metabolically diverse heterotrophic Proteobacteria (31) were abundant in all the colonized sands, which is consistent with other hyporheic microbial communities (22,29,30) as well as previous Hanford 300 Area studies (15)(16)(17), and indicates a central role of these organisms in organic carbon (OC) decomposition across the HC. The abundance of Pseudomonadaceae relative to all Gammaproteobacteria was particularly high in the GWS, which is consistent with a previous sand colonization study in Hanford 300 Area groundwater (32), where Pseudomonadaceae accounted for 60 to 80% of all Proteobacteria.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A subset of these taxa was present in comparable numbers in all three habitats, whereas others showed major variations connected to differential organic matter input and metabolism. Metabolically diverse heterotrophic Proteobacteria (31) were abundant in all the colonized sands, which is consistent with other hyporheic microbial communities (22,29,30) as well as previous Hanford 300 Area studies (15)(16)(17), and indicates a central role of these organisms in organic carbon (OC) decomposition across the HC. The abundance of Pseudomonadaceae relative to all Gammaproteobacteria was particularly high in the GWS, which is consistent with a previous sand colonization study in Hanford 300 Area groundwater (32), where Pseudomonadaceae accounted for 60 to 80% of all Proteobacteria.…”
Section: Discussionsupporting
confidence: 88%
“…Based on this work and recent microbial community assembly studies in the Hanford 300 Area HC (15)(16)(17), deterministic selection imposed by the various DOC sources/ amounts in the three different habitats was expected to lead to distinct microbial assemblages in the colonized sand materials. Stegen et al (15) showed (using highresolution Fourier transform-ion cyclotron resonance mass spectrometry) significant differences in the properties of DOC among groundwater, river water, and hyporheic zone fluids, which were correlated with both microbial respiration and community composition.…”
mentioning
confidence: 91%
“…We hypothesize that physical streambed characteristics, namely, lower permeability, limit the extent to which fluid-entrained microbes can travel, resulting in more spatially constrained communities. Supporting this inference, homogenizing selection was found to play a significant role in microbial community assembly in Columbia River sediments near Hanford, WA (Graham et al, 2017). In contrast to the Colorado River, the sampling location in the Columbia River is characterized by high permeability owing to the Hanford formation underlying the Columbia River (Table 1; Hammond & Lichtner, 2010).…”
Section: /2019jg005189mentioning
confidence: 85%
“…Microbial co-occurrence networks can reveal associations among network members and yield insight into microbiome functioning (Bissett, Brown, Siciliano, & Thrall, 2013;Cardona, Weisenhorn, Henry, & Gilbert, 2016;Faust & Raes 2012;Fuhrman, 2009;). For example, patterns of microbial co-occurrence have been demonstrated for a diverse range of aquatic and terrestrial environments (Banerjee, Baah-Acheamfour et al, 2016;Barberán, Bates, Casamayor, & Fierer, 2012;De Menezes et al, 2015;Graham et al, 2017;Shi et al, 2016). Previous studies using network analysis have often only assessed bacterial communities and not fungal or archaeal communities (Banerjee, Baah-Acheamfour et al, 2016;Barberán et al, 2012;Shi et al, 2016;Vick-Majors, Priscu, & Amaral-Zettler, 2014).…”
Section: Introductionmentioning
confidence: 99%